2002
DOI: 10.1161/hs0202.104474
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Beta Radiation to Prevent Recanalization After Coil Embolization of Cerebral Aneurysms

Abstract: Background and Purpose-Endovascular treatment of cerebral aneurysms, a minimally invasive alternative to surgery, is too often followed by recanalization and recurrences. The purpose of this work was to assess if in situ beta radiation can inhibit recanalization after coil embolization. Methods-Radioactive platinum coils ( 32 P-coils) were produced by ion implantation of 32 P. A single-coil arterial occlusion model was used to compare angiographic and pathological results at 1 to 12 weeks after nonradioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 17 publications
1
84
0
1
Order By: Relevance
“…Well-described in the literature, coil compaction is particularly a problem in high-flow (eg, terminal, bifurcation) aneurysms, resulting in high recanalization and retreatment rates. [27][28][29][30] Finally, the company has an improved second generation of this device that is undergoing preclinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Well-described in the literature, coil compaction is particularly a problem in high-flow (eg, terminal, bifurcation) aneurysms, resulting in high recanalization and retreatment rates. [27][28][29][30] Finally, the company has an improved second generation of this device that is undergoing preclinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the embolic agent could be designed to somehow inhibit or delay the invasion of endothelial cells in favor of mesenchymal cells. 13 …”
Section: Potential Clinical Applicationsmentioning
confidence: 99%
“…This is consistent with the slow rate of endoluminal thrombus organization that occurs in large human cerebral aneurysms, and experimental canine vein pouch aneurysms [3][4][5][6]25 . Other investigators have used lasers to perform external photocoagulation of surgically exposed aneurysms in humans and experimenwww.centauro.it Interventional Neuroradiology 9: [7][8][9][10][11][12][13][14][15][16][17][18][19]2003 tal animals [26][27][28] . Those studies demonstrated fibroblastic obliteration and neoendothelialization of laser photocoagulated aneurysmal ostia within three to six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although these examples represent forms of mechanical injury, experimental studies and clinical experience have both suggested that the healing response ofthe arterial wall is non-specific [14][15][16] . The ability of endothelial injury to promote endovascular healing was recently illustrated in a study of canine vein pouch aneurysms embolized with P 32 ion implanted microcoils 17 . The beta emitting P 32 coils prevented recanalization of embolized aneurysms and promoted formation of a thick neointimal covering over the necks of embolized aneurysms 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation